Land Suitability and Availability Evaluation for Shallot Farming Development in Brebes Regency, Central Java - Dina Martha Susilawati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Land suitability and availability is needed to be evaluated in Brebes Regency because the utilization of unsuitable land area is increasing to pursue high production targets as the impact of increased shallot demand. The objective of this research was to evaluate the land suitability and land availability for shallot farming development in Brebes Regency, an agricultural regency in Java island.  The method used was the matching method between shallot growing pre-requirement criteria from Indonesian Center for Agricultural Land Resources Research and Development (CALRRD) with land quality and characteristics in Brebes Regency.  Since limited data, we used an interpolation techniques from 14 sample point by using geostatistical wizard tool in ArcGIS 10.3 with inverse distance weighting (IDW) method for nutrient retention and climatologicaldata, while soil physical propertiesfrom soil map atribut data ekstraction, meanwhile terain data were constructed from digital topographic maps (countur line). The result indicated that suitable land for shallot farming development was 29.3% or 50,440.7 hectares included in the Moderately Suitable (S2); 55.5% or 95,819.9 hectares in Marginally Suitable (S3); while Not Suitable (N) was 14.8% or 25,678.3 hectares.  The available land for agricultural farming based on legality was 59,076.0 hectares (without considering the existing shallot farming), while the suitable land area on available land was 56,642.6 hectares.  The existing shallot land area was 49,840,3 hectares, so the available and suitable land area on existing land for shallot farming was 49.099,5 hectares, and potential extensification was 6.417,9 hectares as shrubs, grasslands, open land, and forest. The huge potential extensification area was Salem, Bantarkawung and Ketanggungan Sub-districts, it means that those area have an opportunity and potency for agricultural extensification program development for shallot commodities in Brebes Regency in order to enhance the national shallot productivity and food security.  Land suitability and availability is needed to be evaluated in Brebes Regency because the utilization of unsuitable land area is increasing to pursue high production targets as the impact of increased shallot demand. The objective of this research was to evaluate the land suitability and land availability for shallot farming development in Brebes Regency, an agricultural regency in Java island.  The method used was the matching method between shallot growing pre-requirement criteria from Indonesian Center for Agricultural Land Resources Research and Development (CALRRD) with land quality and characteristics in Brebes Regency.  Since limited data, we used an interpolation techniques from 14 sample point by using geostatistical wizard tool in ArcGIS 10.3 with inverse distance weighting (IDW) method for nutrient retention and climatologicaldata, while soil physical propertiesfrom soil map atribut data ekstraction, meanwhile terain data were constructed from digital topographic maps (countur line). The result indicated that suitable land for shallot farming development was 29.3% or 50,440.7 hectares included in the Moderately Suitable (S2); 55.5% or 95,819.9 hectares in Marginally Suitable (S3); while Not Suitable (N) was 14.8% or 25,678.3 hectares.  The available land for agricultural farming based on legality was 59,076.0 hectares (without considering the existing shallot farming), while the suitable land area on available land was 56,642.6 hectares.  The existing shallot land area was 49,840,3 hectares, so the available and suitable land area on existing land for shallot farming was 49.099,5 hectares, and potential extensification was 6.417,9 hectares as shrubs, grasslands, open land, and forest. The huge potential extensification area was Salem, Bantarkawung and Ketanggungan Sub-districts, it means that those area have an opportunity and potency for agricultural extensification program development for shallot commodities in Brebes Regency in order to enhance the national shallot productivity and food security.